EFFECTS OF RICE HUSK ASH AND EGGSHELL ON THE GROWTH AND YIELD OF RED CHILI (Capsicum annuum L.) - Tri Kurniatuti (JARES (Journal of Academic Research and Sciences), 2018)
The purpose of this study was to determine the effect of rice husk ash dosage and eggshell on thegrowth and yield of red chili, and obtain a treatment that gives the best results on fruit red chili plant.The experiment was arranged with Group Random Design (RAK) with factorial design with twofactors and three replications, factor I is dose rice husk ash consists of three levels ie A0: 0 g /plant,A1: 25 gr / plant, A2: 50 g / plant, G3: 75gr / plant. The second factor is the dose eggshell consists of3 levels ie: C0: 0 g / plant, W1: 15 gr / plant and W2: 30 gr / plant. The experiment will have 9combination treatment from those 2 factors. The resutls showed that the provision of rice husk ashgive the significant effect on height plant growth and the number of leaves, the best dose is theprovision of rice husk ash 50 gr / plant. Provision of eggshell give real effect on plant yield of redpepper that is the number of productive branches, number of fruits per plant and fruit weight cropwith the best dosage is 30 gr / plant.